2014
DOI: 10.1039/c4cc00867g
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalysed oxidative C–H/C–H coupling between olefins and simple ethers

Abstract: The first copper-catalysed oxidative alkenylation of simple ethers to construct allylic ethers was successfully achieved. Different substituted olefins and simple ethers could be cross-coupled well to generate the corresponding alkenylation products. Notably, open-chain ethers were also found to be efficient coupling partners in this reaction. This reaction is likely to proceed via a radical process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(72 citation statements)
references
References 61 publications
2
69
0
1
Order By: Relevance
“…Without PPh 3 work up at room temperature, β-peroxylsulfone could be readily isolated in an excellent yield. 18 O isotope labeling experiments revealed that oxygen atom in the product came from dioxygen (eq 9).…”
Section: Model III In Radical Oxidativementioning
confidence: 99%
“…Without PPh 3 work up at room temperature, β-peroxylsulfone could be readily isolated in an excellent yield. 18 O isotope labeling experiments revealed that oxygen atom in the product came from dioxygen (eq 9).…”
Section: Model III In Radical Oxidativementioning
confidence: 99%
“…However, satisfactory monolithic columns were not successfully synthesized. Based on Zou's report [22], we chose 1-propanol/DEGDE as porogenic systems. As a result, available monolithic columns were obtained.…”
Section: Optimization Of Preparation Conditions Of Imidazolium-based mentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxane (POSS) based monoliths have recently been proposed as a new hybrid monolith family in RP chromatography applications carried out in nano/micro-liquid chromatography systems [6][7][8][9][10][11][12][13][14][15][16][17]. These monoliths with high cross-linking density mostly exhibit retention-independent chromatographic separation efficiency and also high mechanical and chemical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These monoliths with high cross-linking density mostly exhibit retention-independent chromatographic separation efficiency and also high mechanical and chemical resistance. In addition to all these features, POSS-based monoliths are compatible with thiol-en chemistry, a novel approach in the literature, which allows the functionalization of a monolith by a one-pot process involving hydrophilic or hydrophobic ligands having single or multiple thiol groups [15][16][17].…”
Section: Introductionmentioning
confidence: 99%